PENERAPAN TERAPI KOMPLEMENTER JUS MENTIMUN DALAM MENURUNKAN TEKANAN DARAH PADA KELUARGA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS PLERED PURWAKARTA - Herwed Nelson; Grace Evelyn; Devita Sonia (Bajang Institute, 2022)
Hypertension or high blood pressure is a condition where the systolic blood pressure is more than 140 mmHg and the diastolic blood pressure is more than 90 mmHg, if not treated it will increase the risk of heart, brain, kidney and stroke disease. According to WHO (2019), the global prevalence of hypertension is 22%, the number of hypertension sufferers in Indonesia has reached 34.11% and continues to increase every year. Riskesdas, (2018) the prevalence of hypertension in West Java is 39.60%, while the measurement results in Purwakarta Regency are 36.79, this prevalence is greater than the prevalence in Indonesia. In the Plered Community Health Center area, data on outpatient hypertension patients was found to be 16.2% (Plered Community Health Center Annual Report, 2022). Researchers aim to provide complementary therapy application of cucumber juice in lowering blood pressure in family members with hypertension. The research used was a Quasi Experiment Design with the design used being a one group pretest – Posttest design. Research results Analysis of the effect of giving cucumber juice on reducing blood pressure in hypertensive families from statistical tests shows the difference between the average systolic blood pressure in the pre-test and post-test intervention groups. The results obtained were p value = 0.000 [p<α (α=0.05)], so it was concluded that there was a difference in the average systolic blood pressure before and after being given cucumber juice. Conclusion: One implementation of nursing in families with hypertension that can be applied by utilizing one of the family's roles and functions (family care function or health maintenance) can be the application of complementary therapy with cucumber juice. This therapy can be carried out independently by the family and even by the sufferer himself, but still with the guidelines taught by the nurse